Factors associated with unplanned readmissions for patients with mental and behavioural disorders in China: a quantitative analysis - Sha Lai; Zechen Wang; Chi Shen; Junfei Feng; Yawei Huang; Xiaolong Zhang; Li Lu; Zhongliang Zhou (Global Health Action)
Background Unplanned readmissions among patients with mental and behavioural disorders (MBDs) disrupt inpatient recovery and impose financial burdens on families and healthcare systems. Objectives To estimate the 31-day unplanned inpatient readmission rates for MBDs in China and identify determinant profiles from the perspective of individual, hospital, and contextual levels. Methods Data from patients with MBDs were collected from the medical records of 99 public hospitals across 10 cities. A total of 49,352 inpatient admissions were analysed based on the proposed conceptual model using multilevel logistic regressions. Results The 31-day unplanned readmission rate (excluding 0–1-day returns) was 8.6% (95% CI: 8.4–8.9%). Determinant profiles differed across the overall group and subgroups. The number of general practitioners within cities was associated with reduced risk of unplanned readmissions. Hospital factors such as facility type and size, human resources, and revenue size were associated with unplanned readmissions only in specific subgroups. Additionally, individual-level factors, including demographic information (e.g. gender, age, marital status, and occupational status), disease-related factors (e.g. primary diagnostic group, condition at admission, and other diagnoses), and clinical characteristics (e.g. length of stay and medical costs), were associated with unplanned readmissions across all subgroups. Conclusion The study emphasises collaborative efforts from health systems, hospitals, and patients to reduce unplanned readmissions for MDBs. Health systems should focus on improving access to care, enhancing quality, and ensuring continuity while providing incentives for hospitals. Additionally, hospitals should prioritise the identification and effective management of their high-risk patients.